2022
DOI: 10.3389/fonc.2022.1081089
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of cuproptosis-related long non-coding RNA signature and personalized therapeutic strategy of breast cancer patients

Abstract: BackgroundBreast cancer (BC) is considered to be one of the primary causes of cancer deaths in women. Cuproptosis was suggested to play an important role in tumor proliferation and tumor immune microenvironment. Therefore, an investigation was conducted to identify the relationship between cuproptosis-related long non-coding RNAs (lncRNAs) and BC prognosis.MethodBased on The Cancer Genome Atlas (TCGA), nine cuproptosis-related lncRNAs were identified by Pearson’s analysis and Cox regression analysis to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…LncRNAs have been implicated in facilitating the evasion of immune surveillance by tumor cells through multiple mechanisms, including the promotion of an immunosuppressive microenvironment 26 28 . Multiple studies used comprehensive analysis to determine the functions of various lncRNAs in tumor immune microenvironment (TIME) in various cancers, such as colon cancer 29 , clear cell renal cell carcinoma 30 , breast cancer 31 , 32 , lung cancer 33 , 34 , thyroid cancer 35 , adrenocortical adenocarcinoma 36 , bladder cancer 37 , and head and neck squamous cell carcinoma 38 . LncRNA NKILA has demonstrated the ability to initiate apoptosis in tumor-specific T cells, thereby impeding their capacity to infiltrate the tumor, leading to tumor immune evasion 39 .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been implicated in facilitating the evasion of immune surveillance by tumor cells through multiple mechanisms, including the promotion of an immunosuppressive microenvironment 26 28 . Multiple studies used comprehensive analysis to determine the functions of various lncRNAs in tumor immune microenvironment (TIME) in various cancers, such as colon cancer 29 , clear cell renal cell carcinoma 30 , breast cancer 31 , 32 , lung cancer 33 , 34 , thyroid cancer 35 , adrenocortical adenocarcinoma 36 , bladder cancer 37 , and head and neck squamous cell carcinoma 38 . LncRNA NKILA has demonstrated the ability to initiate apoptosis in tumor-specific T cells, thereby impeding their capacity to infiltrate the tumor, leading to tumor immune evasion 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the significant prior research has investigated the association between cuproptosis and breast cancer 23 28 . For example, one study identified a risk score derived from nine cuproptosis-related lncRNAs (LRRC8C-DT, TDRKH-AS1, SAMMSON, SIAH2-AS1, WDFY3-AS2, LINC00393, ARHGAP28-AS1, PCAT18, LINC01711), establishing it as an independent prognostic factor for BC and a potential indicator for immunotherapy response 23 .…”
Section: Discussionmentioning
confidence: 99%